Relevancy of blending theory in Science learning during COVID-19 pandemic situation (Siddhajyoti Interdisciplinary Journal, 2022)
This paper focuses on the learning interventions that are traditionally classified as either objectivist or constructivist and there has been an increased predisposition for practitioners to use elements of both paradigms as a blending theory. The previous thinking was that they are opposite to each other. But in the initial phase, the Cronje developed it as the mutual exclusive form. He developed a four-quadrant model and put constructivism and objectivism in a triangular vertex of four theories such as immersion, injection, construction and integration. But later he compared it with learning context such as chaos, complex, knowable and known form with the connecting methods and valuing that use of technology as the blending theory which was supported by wang's model for use of science teaching. Cronje's latest study found that the high use of objectivism/behaviourism and constructivism is an interaction point and is considered as the high study achievement in the present pandemic context of science learning. The finding of this study indicates that if the new instructional model developed by Cronje and Wang can connect with the socio-cultural context of rural students by blending theory, methods and creative technology, it would reduce the educational harm in this pandemic context.